2017
DOI: 10.1016/j.eurpolymj.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Star-shaped lactic acid based systems and their thermosetting resins; synthesis, characterization, potential opportunities and drawbacks

Abstract: Shortcomings of the conventional PLA synthesis methods have encouraged researchers to investigate on alternative methods for PLA synthesis. Utilization of chain extenders is an effective way to achieve high MW polymers. The concept of using star-shaped resins as the reinforced matrices for biocomposites or in biomedical applications is gaining more and more attention day by day. Star-shaped lactic acid based resins are a class of branched resins with a multifunctional core molecule and lactic acid branches. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 145 publications
0
28
0
Order By: Relevance
“…Another route has been to synthesize branched PLA, mainly for the use as thermosets. Different techniques have been employed for inducing branching points in the structure of PLA, including free‐radical branching in the presence of peroxides . The crosslinkable branched‐structure lowers the melt viscosity of the un‐cured resin, which enhances processability of the un‐cured resin and in the same time increases MW of the cured resin which in turn improves the mechanical properties of the cured resin.…”
Section: Introductionmentioning
confidence: 99%
“…Another route has been to synthesize branched PLA, mainly for the use as thermosets. Different techniques have been employed for inducing branching points in the structure of PLA, including free‐radical branching in the presence of peroxides . The crosslinkable branched‐structure lowers the melt viscosity of the un‐cured resin, which enhances processability of the un‐cured resin and in the same time increases MW of the cured resin which in turn improves the mechanical properties of the cured resin.…”
Section: Introductionmentioning
confidence: 99%
“…Teng and Nie et al reported the controlled drug-release behavior of star-shaped PLLAs with a SB core [22]. Recently, network polymers derived from terminal functionalized star-shaped biodegradable polyesters have gathered considerable attention since the curing reaction of their at least three functional groups easily generates crosslinked structures and the crosslinking density can be controlled by changing the arm length [3,13,[29][30][31][32][33][34][35][36][37][38]. For example, Storey et al reported the networks prepared by the crosslinking reaction of hydroxy-terminated 3-armed random copolymers of D,L-LA and CL with L-lysine diisocyanate [30].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with linear analogs of equal molecular weight, they have a higher concentration of functional end groups, and often exhibit lower viscosities, different thermal and mechanical properties and improved physical processability, as their properties are more influenced by arm length than the total molecular weight. Recently, a number of researchers have focused on star-shaped biodegradable/biocompatible polyesters for biomedical applications, including drug delivery, gene delivery, tissue engineering, diagnosis and medical devices [1][2][3]. Until now, a variety including drug delivery, gene delivery, tissue engineering, diagnosis and medical devices [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations